Trademark Sales Study as Boedel Bankrupt by the Curator - Aldy Wicaksono; Ahmad Sudiro (Dinasti Research, 2025)
Trademarks are included in the Intellectual Property Rights (IPR) regime in Indonesia because trademark rights are always attached to economic rights. This study uses a normative method by collecting secondary data. Qualitative analysis was carried out on secondary data to obtain conclusions about the Nyonya Meneer brand as an intangible asset owned by PT Nyonya Meneer which is bankrupt based on the Commercial Court Decision. As a result of the law of PT Nyonya Meneer being bankrupt, the Curator carried out the settlement and management of the bankrupt estate including the Nyonya Meneer brand by auction through private sales with an appraisal value of Rp. 200 billion to Rp. 10.25 billion. It is hoped that the government will make a regulation related to the valuation regulations for IPR as well as regulations related to the transfer of IPR as bankrupt assets and create a special appraisal institution to provide legal certainty for the curator in carrying out his duties and authorities.